Effects of Hot Nights on Mortality in Southern Europe. Issue 4 (2nd April 2021) - Royé, Dominic; Sera, Francesco; Tobías, Aurelio; Lowe, Rachel; Gasparrini, Antonio; Pascal, Mathilde; de'Donato, Francesca; Nunes, Baltazar; Teixeira, Joao Paulo
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: There is strong evidence concerning the impact of heat stress on mortality, particularly from high temperatures. However, few studies to our knowledge emphasize the importance of hot nights, which may prevent necessary nocturnal rest. Objectives: In this study, we use hot-night duration and excess to predict daily cause-specific mortality in summer, using multiple cities across Southern Europe. Methods: We fitted time series regression models to summer cause-specific mortality, including natural, respiratory, and cardiovascular causes, in 11 cities across four countries. We included a distributed lag nonlinear model with lags up to 7 days for hot night duration and excess adjusted by daily mean temperature. We summarized city-specific associations as overall-cumulative exposure–response curves at the country level using meta-analysis. Results: We found positive but generally nonlinear associations between relative risk (RR) of cause-specific mortality and duration and excess of hot nights. RR of duration associated with nonaccidental mortality in Portugal was 1.29 (95% confidence interval [CI] = 1.07, 1.54); other associations were imprecise, but we also found positive city-specific estimates for Rome and Madrid. Risk of hot-night excess ranged from 1.12 (95% CI = 1.05, 1.20) for France to 1.37 (95% CI = 1.26, 1.48) for Portugal. Risk estimates for excess were consistently higher than for duration. Conclusions: This study provides new evidence that, over a wider range of locations, hot night indices are strongly associated with cause-specific deaths. Modeling the impact of thermal characteristics during summer nights on mortality could improve decisionmaking for preventive public health strategies.